Gender budgeting: a vital element for ensuring sustainable development - Bilyk, Olena; Karkovska, Veronika; Khim, Mariia Kimsanivna (Sustainability in Debate, 2022)
The article aims to highlight the latest approaches to the introduction of countries gender budgeting. The authors propose the application of the method of ranking countries based on 4 key indicators related to the gender gap (Economic participation and opportunity, Educational attainment, Health and survival, Political empowerment) of the Global gender gap index and then analyse the result considering the level of socio-economic development of each country. Ten sample countries were randomly chosen. The results of the study confirmed the mutual influence between the gender gap and socio-economic development. The proposed method of ranking countries compared to socio-economic, political and environmental development allows countries with a high value of the gender gap index to offer specific tools to reduce it. The research conducted can help improve existing practices, facilitate initiatives to develop gender parity and further work on geographical and sectoral orientation.